2019
DOI: 10.1039/c9ra06577f
|View full text |Cite
|
Sign up to set email alerts
|

Surface and thermal properties of synthesized cationic poly(ethylene oxide) gemini surfactants: the role of the spacer

Abstract: Synthesis of new cationic poly(ethylene oxide) gemini surfactants containing flexible and rigid spacer groups to tolerate harsh reservoir condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Because earlier reports suggested that surfactants can reduce the clay swelling, however, most of the surfactants degrade at highsalinity and high-temperature conditions. However, these surfactants have shown excellent thermal stability and salt resistance in high-temperature and high-salinity conditions which has been reported earlier in our previous publications (Hussain et al, 2019b). The addition of ethoxy groups increase their salt tolerance and make surfactant soluble in high-salinity brines.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Because earlier reports suggested that surfactants can reduce the clay swelling, however, most of the surfactants degrade at highsalinity and high-temperature conditions. However, these surfactants have shown excellent thermal stability and salt resistance in high-temperature and high-salinity conditions which has been reported earlier in our previous publications (Hussain et al, 2019b). The addition of ethoxy groups increase their salt tolerance and make surfactant soluble in high-salinity brines.…”
Section: Introductionmentioning
confidence: 54%
“…Figure 1 shows the synthetic scheme and structure of the synthesized surfactants. Further details of synthetic methodology and characterization are published in our previous publication (Hussain et al, 2019b). These surfactants have the same functionalities except the spacer group.…”
Section: Materials and Experimental Program Materialsmentioning
confidence: 99%
“…Formally, geminis that are asymmetric (e.g., those with a lysine spacer) are classified as geminoid or gemini-like surfactans [ 36 , 37 ]. Hydrophobic fragments (tails) used in gemini surfactants vary in length (usually 8–20), structure (straight or branched chain) [ 38 ], and saturation [ 39 ]; tails can be fluorinated [ 40 ], contain poly(ethylene oxide) [ 41 ], cholesterol [ 42 ], or aromatic backbones [ 43 ]. Gemini surfactants are an intriguing group of compounds owing to their increased solubility in water, superior surface tension reduction power, reduced proximity between hydrophobic groups, lower critical micellar concentration (by one or more magnitudes), and superior wetting characteristics as compared to the corresponding single chain (monomeric) surfactants, which makes them convenient candidates for pharmaceuticals formulations [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, Hussain et al studied the thermal degradation of three cationic poly(ethylene oxide) gemini surfactants containing flexible and rigid spacers. The thermal gravimetric analysis showed a degradation temperature higher than that observed in an oilfield (90 • C) [102].…”
Section: Applicationsmentioning
confidence: 63%